Phone-based motivational interviewing intervention among patients undergoing cardiac rehabilitation: A randomized controlled trial in China - Yu Wang; Chintana Wacharasin; Khemaradee Masingboon (Belitung Nursing Journal, 2026)
Background: Maintaining regular physical activity (PA) is a critical challenge for patients undergoing cardiac rehabilitation (CR), as inadequate adherence can lead to adverse outcomes, including disease recurrence. Enhancing motivation is key to improving PA adherence. Motivational interviewing (MI) has been shown to overcome psychological barriers by building intrinsic motivation. However, there is a need to explore how to integrate MI techniques with digital technology to enhance intervention accessibility and leverage the strengths of both approaches. Objective: This study aimed to evaluate the effects of a hybrid intervention model integrating phone-based motivational interviewing with mobile phone-based management on motivation and physical activity in patients undergoing CR. Methods: This pilot randomized controlled trial was conducted in China between January and June 2024, involving 52 patients undergoing cardiac rehabilitation. The intervention group (n = 25) received usual care plus a 4-week phone-based motivational interviewing intervention, which included a face-to-face session, weekly phone MI sessions (OARS technique), and personalized support via WeChat. The control group (n = 27) received only usual cardiac rehabilitation guidance. Outcomes measured were steps/day (using a smart band) and motivation, assessed using the Behavioral Regulation in Exercise Questionnaire-2 (BREQ-2). Two-way repeated-measures ANOVA was used for data analysis. Results: Compared with the control group, the intervention group showed a significant interaction effect of Group*Time on both steps/day (p <0.001, ηp2 = 0.706) and the BREQ-2 (RAI) (p <0.001, ηp2 = 0.349). The intervention group’s daily steps significantly increased from 3582.80 ± 649.59 to 9444.79 ± 1413.72 (p <0.001). Conclusion: This study indicates that a phone-based motivational interviewing intervention delivered by trained researchers can effectively increase physical activity levels and enhance autonomous motivation for PA in CR patients. This approach provides a scalable model for the routine care of cardiac rehabilitation patients, especially in resource-limited settings. For nursing practice, the findings highlight the importance of incorporating MI as a core skill and utilizing a hybrid, technology-supported care model to extend continuous professional support into patients’ homes. Trial Registry Number: Chinese Clinical Trial Registry (ChiCTR2400079877)